2013
DOI: 10.1124/mol.113.087106
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Knockout of Kalirin-7 Leads to Increased Rates of Cocaine Self-Administration

Abstract: Kalirin-7 (Kal7) is a Rho-guanine nucleotide exchange factor that is localized in neuronal postsynaptic densities. Kal7 interacts with the NR2B subunit of the NMDA receptor and regulates aspects of dendritic spine dynamics both in vitro and in vivo. Chronic treatment with cocaine increases dendritic spine density in the nucleus accumbens (NAc) of rodents and primates. Kal7 mRNA and protein are upregulated in the NAc following cocaine treatment, and the presence of Kal7 is necessary for the normal proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 59 publications
(91 reference statements)
0
15
0
Order By: Relevance
“…While some of these abnormalities are shared with Kal7 KO mice, others are not (Kiraly et al 2010;Kiraly et al 2013;Lemtiri-Chlieh et al 2011;Ma et al 2008;Mazzone et al 2012); shared traits, such as the decrease in anxiety-like behavior and impaired contextual fear learning, may reflect the loss of Kal7. Since several of the traits exhibited by KalSR KO mice involve aberrant pituitary hormone secretion and several behavioral phenotypes suggest hypothalamic-pituitary-adrenal involvement, we chose to test the effects of eliminating Kalirin expression only in cells which express POMC at some time during development or in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some of these abnormalities are shared with Kal7 KO mice, others are not (Kiraly et al 2010;Kiraly et al 2013;Lemtiri-Chlieh et al 2011;Ma et al 2008;Mazzone et al 2012); shared traits, such as the decrease in anxiety-like behavior and impaired contextual fear learning, may reflect the loss of Kal7. Since several of the traits exhibited by KalSR KO mice involve aberrant pituitary hormone secretion and several behavioral phenotypes suggest hypothalamic-pituitary-adrenal involvement, we chose to test the effects of eliminating Kalirin expression only in cells which express POMC at some time during development or in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation involves knockout of Kal7 in the widespread population of cells that produced POMC at some time during development - hippocampus, cortex, and amygdala are obvious candidates. Based on what is known about the role of Kal7 in other neurons, the absence of Kal7 presumably affects synapses with excitatory inputs onto functionally compromised dendritic spines of neurons no longer expressing Kalirin (Kiraly et al 2011;Kiraly et al 2010;Kiraly et al 2013;Lemtiri-Chlieh et al 2011;Ma et al 2008;Mazzone et al 2012). There are major projections from the arcuate nucleus of endorphin- and melanotropin-containing fibers into the amygdala, hippocampus and cortex which could all be altered by depressed Kalirin levels (Balthasar 2006;Herman et al 2003;King and Hentges 2011;Vermetten and Bremner 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Kiraly and colleagues went on to show that expression of larger kalirin splice variants, kalirin-9 and -12, is upregulated in the Kal7 KO mice following cocaine administration (Kiraly et al, 2013). They also found that expression of the NMDAR subunit NR2B is upregulated following cocaine administration in wild-type, but not Kal7 KO mice (Kiraly et al, 2013).…”
Section: Kalirin and Other Disordersmentioning
confidence: 99%
“…They also found that expression of the NMDAR subunit NR2B is upregulated following cocaine administration in wild-type, but not Kal7 KO mice (Kiraly et al, 2013). Furthermore, chronic treatment with cocaine has been shown to alter the expression profile of specific kalirin isoforms by altering usage of isoform-specific promoters.…”
Section: Kalirin and Other Disordersmentioning
confidence: 99%
“…Incentive sensitization, the ability to rapidly learn to self-administer cocaine, was also impaired. Interestingly, constitutive Kal-7 knockout enhanced cocaine SA (Kiraly et al, 2013), which might be due to compensations by other kalirin isoforms.…”
Section: Drug-induced Neuroplasticitymentioning
confidence: 99%